Penetration tester's open source toolkit (Syngress Pub., 2006)
Penetration testing a network requires a delicate balance of art and science. A penetration tester must be creative enough to think outside of the box to determine the best attack vector into his own network, and also be expert in using the literally hundreds of tools required to execute the plan. This book provides both the art and the science.